2005
DOI: 10.1111/j.1740-8261.2005.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Retrograde Cholangio‐pancreatography in Healthy Beagles

Abstract: Endoscopic retrograde cholangiography and pancreatography was performed in seven healthy Beagles to assess the common bile duct and the accessory pancreatic duct after retrograde filling with an iodine contrast medium. All dogs had a major and a minor duodenal papilla. One Beagle had additionally an accessory papilla. The diameter of the contrast filled ducts was measured at three defined measure points (MP1-3) in ventrodorsal radiographs and left lateral radiographs. In ventrodorsal radiographs of endoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 21 publications
(27 reference statements)
6
33
0
Order By: Relevance
“…Dogs were postitioned in left recumbency and conventional gastroduodenoscopy was performed followed by side‐view endoscopy for intraduodenal examination and cannulation of major and minor papillae. For endoscopic retrograde cholangio‐pancreatography with fluoroscopy, the dogs were positioned in dorsal recumbency 5 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs were postitioned in left recumbency and conventional gastroduodenoscopy was performed followed by side‐view endoscopy for intraduodenal examination and cannulation of major and minor papillae. For endoscopic retrograde cholangio‐pancreatography with fluoroscopy, the dogs were positioned in dorsal recumbency 5 …”
Section: Methodsmentioning
confidence: 99%
“…E ndoscopic retrograde cholangio‐pancreatography is a combination of endoscopy and fluoroscopy to perform radiographic imaging of the biliary and pancreatic duct systems. This technique is technically possible in dogs 1–5 . In humans, endoscopic retrograde cholangiography is used for determination of the cause of extrahepatic cholestasis, and for preparation, implementation, and postoperative control of gallbladder surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Endotoxemia and bacterial translocation may occur because the lack of luminal bile salts may promote increased intestinal permeability and intestinal bacterial overgrowth, which can overwhelm the hepatic reticuloendothelial system. In 2005, Spillmann et al 28,29 first reported successfully perform-ing diagnostic ERCP in 7 clinically normal research dogs and 30 canine patients with vague gastrointestinal signs. These procedures often help stabilize the patient, which can facilitate a more definitive permanent decompressive procedure at a later time.…”
mentioning
confidence: 99%
“…To exclude potential differentials before performing an invasive laparotomy, the use of various imaging modalities has been reported. Retrograde cholangiopancreatography can be performed in children and adult dogs, although the authors describe technical complications in very small patients rendering this less suitable for use in very small veterinary patients . Magnetic resonance cholangiography and intraoperative cholangiography has also been mentioned .…”
Section: Discussionmentioning
confidence: 99%